Pedagogical strategy to reduce the school dropout rate in 15-year-old adolescents (Revista Ciencia Agraria, 2022)
The problem of school dropout brings with it innumerable effects that make those who are faced with it living different experiences; it is important to detect the factors with the highest incidence and the emotions or experiences that generates it in order to provide alternative solutions that can be implemented to mitigate this phenomenon. This is how this research proposal takes places, which seeks to design a pedagogical strategy that allows minimizing the school dropout rate in 15-year-old adolescents from an educational institution in Montelíbano, Córdoba. This study is qualitative in nature, with an action-research methodology, descriptive type, with a selected sample of 13 adolescents for the application of a semi-structured interview as an instrument for collecting information. Finally, the results are analyzed from the qualitative research approach, and different pedagogical activities such as: workshops for parents, students and teachers about the importance of staying in school, socio-emotional talks to students and motivational forums are carried out.
Keywords: adolescence; school dropout; educational strategy; school parents; relationship